Between Transaction and Partnership: The Juridical Discrepancy in MLM Member Onboarding Based on DSN-MUI Fatwas in Makassar - Misbahuddin; Rifai, Ahmad Faizal; Thahir, Muhammad Nasir (Parewa Saraq: Journal of Islamic Law and Fatwa Review, 2025)
This research aims to analyze the recruitment methods used by Multi-Level Marketing (MLM) practitioners and to assess the relevance and compliance of these practices with the contractual provisions outlined in DSN-MUI fatwas. Employing a qualitative research approach, data were collected through observation, interviews, and documentation involving MLM companies in Makassar. The findings reveal that recruitment strategies commonly involve personal selling, hypnoselling techniques, promises of success, and flexing or marketing signaling. Notably, at the closing stage, companies apply the al-Ba’i Murabahah contract with prospective members, framing it as a business partnership within the same company. However, al-Ba’i Murabahah is inherently a transactional contract and not suited for intermediation purposes. The study demonstrates that the application of DSN-MUI fatwa-based contracts in MLM recruitment has not yet fully aligned with Sharia principles, particularly in terms of intermediation contracts. The appropriate model for member recruitment should be based on Mudharabah, where prospective members contribute effort, time, and skills to product distribution without initial capital investment. This study offers a novel critique of fatwa implementation in the context of MLM operations, highlighting the juridical disconnect between theoretical contract types and actual recruitment practices. The findings have practical implications for Sharia supervisory bodies and MLM operators to realign recruitment mechanisms with valid intermediation contracts, ensuring greater compliance with Islamic commercial ethics.